IMPROVING THE STUDENTS‘ WRITING ABILITY THROUGH SPIDER WEB EXTENSION TECHNIQUE - Natsir, Ratu Yulianti (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2014)
This study aimed to explain the improvement of the students’writing ability through the implementation  of “Spider Web Extension ” technique  in teaching writing.The writer used a classroom action research principle to collect the data that consisted of two cycles. Each cycle consisted of four meetings. The location this research was taken at the eleventh grade students of  SMA Tridharma MKGR Makassar. The students‘ number of the class is 36 students and the class consist of 20 women and 16 men. The findings indicated that the implementation of Spider Web Extension technique could improve the students' ability in writing test. Before giving implementation the writer gave the students diagnostic test and the mean score of diagnostic test was 45.27. Then the writer conducted the first cycle and the second cycles, and the result showed that the students' scores in the first and second cycles improved. In the first cycle, the mean score of students was 58.8 , mean while the mean score of students in the second cycle was 71.1 It could be concluded that the improvement students‘ writing ability through Spider Web Extension Technique in terms of content and organization are significantly improved.